Mellow Babies: A Randomised Feasibility Trial of an Intervention to Improve the Quality of Parent-Infant Interactions and Parental Mental Wellbeing - Lucy Thompson; Philip Wilson (MDPI AG, 2024)
Mellow Babies aims to improve mothers' mental wellbeing and the quality of their interactions with their baby. The feasibility of a definitive trial of Mellow Babies was assessed using a waiting-list randomised pilot trial (Clinicaltrials.gov: NCT02277301). Mothers with substantial health/social care needs and a child aged <13 months were randomly allocated either to a 14-week Mellow Babies programme or to receive usual care whilst on a waiting list for the intervention. Rates of recruitment and retention as well as participants' views of their experience in this study were recorded. Outcomes were parenting behaviour, assessed by the blind-rated Mellow Parenting Observation System (primary) and self-report maternal wellbeing pre- and post-intervention/waiting period. We recruited 38 eligible participants: 36 (95%; 18 intervention, 18 control) completed baseline measures, and 28 (74%; 15 intervention, 13 control) provided post-intervention data. Two practitioners took part in feedback interviews. Intervention participants had significantly more positive interactions with their babies at post-intervention compared to those in the control group (p = 0.019), adjusted for pre-intervention scores. There was no significant improvement in mothers' mental wellbeing on any measure. A definitive trial of Mellow Babies is feasible and should include longer follow up of mothers and the opportunity for fathers to take part.